Celiac Disease and Schizophrenia - Richard P Conti, Jacqueline M Arnone (Journal of Medical Biomedical and Applied Sciences, 2016)
The relationship between schizophrenia and celiac disease (CD) has been reported in the research literature for over 70 years. CD is a T-cell mediated autoimmune inflammatory disease of the small intestine and is activated by the consumption of prolamins found in wheat, rye, oats or barley in genetically predisposed individuals. Incidence and prevalence rates for CD in the United States (US) are widespread, affecting 1% of the aggregate population in not at-risk groups, or1 out of 133 persons. Gluten, the trigger for CD and cause for damage to the lining of the small intestine, has been demonstrated to impair the nervous system. Neurologic disorders including ataxia, epilepsy and headache have been well documented in the literature. Psychiatric conditions including depression, anxiety and schizophrenia have also been studied with great interest among adults and children with CD. Additionally, impaired cognitive function has also been reported in individuals with CD and schizophrenia. Past and current studies on schizophrenia have demonstrated a reduction in psychotic symptoms following adherence to a gluten-free diet, however studies with smaller sample sizes showed no significant differences. Recommendations for future empirical research to further investigate the relationship between schizophrenia, cognitive function and CD are discussed.